MODEL PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERWAWASAN MULTIKULTURAL: STUDI PADA GURU PENDIDIKAN AGAMA ISLAM MTSN TAMBAK BERAS JOMBANG - Asrori, Mohammad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2017)
As a country endowed with a multifaceted cultural wealth and tribes and nations, the study of multicultural education and religion is an inseparable unity. One place that is quite representative in seeing learning model multicultural vision of Islam is MTSN Tambak Beras Jombang. Pesantren-based Madrasah has long run a multicultural vision of Islamic religious education though is not formally written into the curriculum developed. Islamic religious education in a multicultural vision of MTSN Tambak Beras Jombang become one of the important features in fostering the values of social pluralism in a nation and a state without losing the values of Islamic